Precambrian Plate Tectonics in Northern Hudson Bay: Evidence From P and S Wave Seismic Tomography and Analysis of Source Side Effects in Relative Arrival‐Time Data Sets. Issue 7 (5th July 2018) - Liddell, Mitch V.; Bastow, Ian; Rawlinson, Nicholas; Darbyshire, Fiona; Gilligan, Amy; Watson, Emma
Abstract: The geology of northern Hudson Bay, Canada, documents more than 2 billion years of history including the assembly of Precambrian and Archean terranes during several Paleoproterozoic orogenies, culminating in the Trans‐Hudson Orogen (THO) ∼1.8 Ga. The THO has been hypothesized to be similar in scale and nature to the ongoing Himalaya‐Karakoram‐Tibetan orogen, but the nature of lithospheric terrane boundaries, including potential plate‐scale underthrusting, is poorly understood. To address this problem, we present new P and S wave tomographic models of the mantle seismic structure using data from recent seismograph networks stretching from northern Ontario to Nunavut (60–100 ∘ W and 50–80 ∘ N). The large size of our network requires careful mitigation of the influence of source side structure that contaminates our relative arrival time residuals. Our tomographic models reveal a complicated internal structure in the Archean Churchill plate. However, no seismic wave speed distinction is observed across the Snowbird Tectonic Zone, which bisects the Churchill. The mantle lithosphere in the central region of Hudson Bay is distinct from the THO, indicating potential boundaries of microcontinents and lithospheric blocks between the principal colliders. Slow wave speeds underlie southern Baffin Island, the leading edge of the generally high wave speed Churchill plate. This is interpreted to be Paleoproterozoic material underthrust beneath Baffin Island in a modern‐style subduction zone setting. Key Points: Evidence of Precambrian plate‐scale underthrusting beneath Baffin Island Microplates within the Trans‐Hudson Orogen are imaged, complicating the two‐plate hypothesis; no seismic distinction at the STZ is observed Subducting slabs can contaminate relative arrival time residuals and frequency content; we analyze the effect and show that it may be mitigated